Predição de vida em fadiga de uma roda de caçambas utilizando mecânica da fratura linear elástica - Bruno Lopes Barcelos (2018)
This work presents the study of crack propagation in the welded joint of a bucket wheel that failed in field after approximately one year of operation. This joint is located at the transition between the hub of the drive shaft and the main body of the bucket wheel. The concepts of Linear Elastic Fracture Mechanics were adopted in the analysis. The loads resulting from the material excavation process were applied to a finite element model, from which the stresses in the fractured region were obtained. Some aspects related to the welded joint were considered in the analysis, such as the occurrence of residual stresses in the structure and the magnification factor of the stress intensity factor due to the weld geometry. The crack closure phenomenon was also considered, due to the presence of compressive stresses in the loading cycle. Due to the peculiar geometry of the welded joint, the stress intensity factor was numerically obtained for the semi-elliptical cracks and through-thickness cracks considered, taking into account tensile and shear loads. The propagation was evaluated with the preferential direction of both the depth and the length of the crack, using the Walker equation (consideration of the stress ratio effect) for determining the propagation rate. A fatigue life consistent with the estimation of the number of cycles until the failure of the bucket wheel was obtained when considering the propagation of a preexisting crack in the structure in a field of residual tensile stresses across the thickness of the plate and along the weld bead. It was evaluated that fatigue life based on SN curves, for a weld detail similar to the weld joint under study, was higher than the estimated number of cycles until the bucket wheel failure, indicating that some defect may have remained after manufacture of the wheel and compromised its useful life